"And I Think That We Can Fix It": Mental Models Used in High-risk Surgical Decision Making. Issue 4 (April 2015) - Kruser, Jacqueline M.; Pecanac, Kristen E.; Brasel, Karen J.; Cooper, Zara; Steffens, Nicole M.; McKneally, Martin F.; Schwarze, Margaret L.
Abstract : Objective: To examine how surgeons use the "fix-it" model to communicate with patients before high-risk operations. Background: The "fix-it" model characterizes disease as an isolated abnormality that can be restored to normal form and function through medical intervention. This mental model is familiar to patients and physicians, but it is ineffective for chronic conditions and treatments that cannot achieve normalcy. Overuse may lead to permissive decision making favoring intervention. Efforts to improve surgical decision making will need to consider how mental models function in clinical practice, including "fix-it." Methods: We observed surgeons who routinely perform high-risk surgery during preoperative discussions with patients. We used qualitative content analysis to explore the use of "fix-it" in 48 audio-recorded conversations. Results: Surgeons used the "fix-it" model for 2 separate purposes during preoperative conversations: (1) as an explanatory tool to facilitate patient understanding of disease and surgery, and (2) as a deliberation framework to assist in decision making. Although surgeons commonly used "fix-it" as an explanatory model, surgeons explicitly discussed limitations of the "fix-it" model as an independent rationale for operating as they deliberated about the value of surgery. Conclusions: Although the use of "fix-it" is familiar for explaining medical information to patients, surgeons recognize that the model can be problematic for determining the value of an operation. Whether patients can transition between understanding how their disease is fixed with surgery to a subsequent deliberation about whether they should have surgery is unclear and may have broader implications for surgical decision making. Abstract : The "fix-it" model of decision making assumes that medical conditions are acute abnormalities that can be readily and completely addressed through medical intervention. This model is familiar to physicians and patients, but surgeons view it as problematic for complex, high-risk surgical decisions.